Progressivismens barnecentrering, hvide børn og ikke-hvide voksne: Review-essay i anledning af Thomas D. Fallaces bog Race and the Origins of Progressive Education, 1880-1929 - Øland, Trine (Tidsskrift for Professionsstudier, 2021)
This essay expose and discuss Thomas D. Fallace’s explorations of the intellectual history of early US progressive education in order for Danish welfare professions to think about what referencing progressivism and Dewey may be associated with. Despite of pluralistic openings, it is depicted how the assumption that all human beings and all societies go through a development from savagery to civilization, and that non-white groups are stuck in early stages of that development, still haunts progressivism. The ethnocentric and racial assumptions were at first operative in the quest to optimize schooling for non-white pupils, e.g., in the colonies. Later on, progressivism concentrates on white middle class pupils in the private sector of schooling, although non-whites appear as a target group later in history.